Penerapan Model Pembelajaran ROAR (Read, Observe, Auditory, Review) Meningkatkan Pemahaman Konsep Siswa - Emmi Azis; Andi Muhammad Irfan Taufan Asfar; Marliah Rianti; Andi Muhammad iqbal Akbar Asfar; Hasanuddin Hasanuddin; Andi Sitti Aisyah Nur (ILIN Institute Makassar, 2020)
The ROAR learning model is learning that gives students the broadest opportunity to develop concepts, pre-existing ideas become new concepts. The concept is built through direct observation because during learning the teacher presents examples of reality so students will be more critical with the concepts of reality, so that in the end they are able to connect the material based on the concept of reality they are building. This integration aims to have concepts related so that the meaningfulness of learning can be achieved. This study is an experimental study with a nonequivalent control group design with a research focus on social studies subject material in junior high school 8th grade. The results of the analysis of the test analysis show that the application of the ROAR learning model has a consistent impact on students' conceptual understanding abilities. Positive responses from teachers and students to the application of the ROAR learning model as an alternative solution in supporting success in improving the ability to understand concepts that have implications for student motivation and learning achievement.